Sun Protection Factor Activity of Crude Extract, Nanoparticle Extract, and Lyophilised Powder of Arabian Bidara Leaves (Ziziphus spina-christi (L.) Desf.) - Budiati, Anarisa; Kartiningsih; Lady Auria Ananova; Theresia Andrian (Faculty of Pharmacy Universitas Pancasila, 2025)
Arabic Bidara Leaves (Ziziphus spina-christi (L.) Desf.) contain flavonoids, including quercetin, which has SPF properties. The goal of this research was to examine the properties and SPF activity of crude extract, nanoparticle extract, and lyophilized powder of Arabian Bidara Leaves. Arabian Bidara Leaves were extracted using the UAE technique with 70% ethanol solvent. The crude extract was converted into nanoparticle extract using the ionic glass process and then freeze dried to produce lyophilized powder. Then the properties and SPF value were investigated. The study found that the crude extract of Arabian Bidara Leaves has a brownish green color, 10.42%±0.36 water content, 4.68±0.01 pH, and 19.98±0.15 SPF. The nanoparticle extract has a clear yellow color, distinct odor, liquid form, and can be stored for 5 days without sediment formation. It has a particle size of 268.6 nm±3.75, polydispersity index of 0.547±0.06, zeta potential of -6.07 mV, adsorption efficiency of 89.60%, spherical morphology, and an SPF value of 29.96±0.69. The lyophilized powder is brown, flake-shaped, and has an SPF of 29.27±0.76. The results of this investigation show that the leaves of the Arabian bidara have SPF activity in the ultra protection category.